The rights and personal freedoms – the main value in the sphere of criminal process (International relations and international law Journal, 2018)
Ensuring the rights of the personality is especially actual in the sphere of criminal process, as in this sphere of imperious activity of government bodies, essential restrictions and even constitutional violations cases, the right of the personality arise and are shown. Here application of various measures of criminal procedure coercion, including measures of restraint which significantly limit the rights and legitimate interests of the personality, involved in the sphere of criminal justice possibly. Each of participating in investigation (citizen of the Republic of Kazakhstan, and equally in the foreigner or the stateless person) is the individual possessing advantage and the inalienable rights belonging from the birth. The state can set laws restrictions of the rights only for the purpose of due recognition and respect of the rights of others and satisfaction of fair requirements of morals and a public order in democratic society.Key words: personality, rights and freedoms of the person, concept, legal policy.